Alteration of miRNA expression in a sulfur mustard resistant cell line. (1st September 2018) - Rothmiller, Simone; Wolf, Markus; Worek, Franz; Steinritz, Dirk; Thiermann, Horst; Schmidt, Annette
Highlights: SM resistance induced miRNA expression alterations. 49 miRNAs were up- and 29 significantly downregulated in SM-resistant keratinocytes. Out of these, 36 miRNAs belong to 15 different miRNA families. Specific miRNAs may play a role in the resistance mechanism against SM. miR-181 mimic further improved cell survival after SM treatment in resistant cells. Abstract: Background: MicroRNAs (miRNAs) are responsible for post-transcriptional control of protein expression. Numerous miRNAs have been identified to be responsible for the resistance of tumor cells to cytostatic drugs. Possibly, the same miRNAs also play a role in the sulfur mustard (SM)-resistance of the keratinocyte cell line HaCaT/SM as alkylating cytostatics exhibit similar cytotoxic effects as SM. Methods: Basal expression levels of 1920 miRNAs in total were analyzed in HaCaT/SM compared to the origin human keratinocyte cell line HaCaT. The effect for selected miRNAs on cell survival was analyzed using antagomirs for ectopic miRNA level decrease or miRNA mimics for increase. Cell survival was calculated as SM dose-dependent-curves. Results: Out of 1920 miRNAs analyzed, 49 were significantly up- and 29 were significantly downregulated in HaCaT/SM when compared to HaCaT controls. Out of these, 36 could be grouped in miRNA families. Most of the 15 miRNA family members showed either a common increase or decrease. Only the members of miR-10, miR-154, miR-430 and miR-548 family showed an inconsistent picture. The ectopic increase of miR-181 in HaCaT/SM had a positive effect on cell survival in the presence of SM. Conclusion: In summary, the extensive differences in miRNA expression pattern between these cell lines indicate that specific miRNAs may play a role in the resistance mechanism against sulfur mustard. The miR-125b-2 and miR-181b alone are not responsible for the resistance development against SM, but an ectopic increase of miR-181 even enhances the SM resistance of HaCaT/SM. Improving the resistance in normal keratinocytes by treatment with either both miRNAs together or a different combination might be used as an initial step in development of an innovative new drug or prophylactic agent against SM.